2015
DOI: 10.1016/j.virol.2015.02.035
|View full text |Cite
|
Sign up to set email alerts
|

An anti-G protein monoclonal antibody treats RSV disease more effectively than an anti-F monoclonal antibody in BALB/c mice

Abstract: Respiratory syncytial virus (RSV) belongs to the family Paramyxoviridae and is the single most important cause of serious lower respiratory tract infections in young children, yet no highly effective treatment or vaccine is available. To clarify the potential for an anti-G mAb, 131-2G which has both anti-viral and anti-inflammatory effects, to effectively treat RSV disease, we determined the kinetics of its effect compared to the effect of the anti-F mAb, 143-6C on disease in mice. Treatment administered three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 50 publications
1
68
1
Order By: Relevance
“…A murine anti-F protein MAb (143-6C) had no such effect. In a similar model, using RSV line 19F (known to cause increased airway hyperreactivity and mucus hyperproduction in mice), an anti-G protein MAb improved breath distension of peripheral arteries (pulse oximetry) (37). These studies emphasize the anti-inflammatory activity of MAbs targeting the RSV G protein CCD.…”
Section: Pharmacologymentioning
confidence: 80%
See 1 more Smart Citation
“…A murine anti-F protein MAb (143-6C) had no such effect. In a similar model, using RSV line 19F (known to cause increased airway hyperreactivity and mucus hyperproduction in mice), an anti-G protein MAb improved breath distension of peripheral arteries (pulse oximetry) (37). These studies emphasize the anti-inflammatory activity of MAbs targeting the RSV G protein CCD.…”
Section: Pharmacologymentioning
confidence: 80%
“…An important unmet need is for a post-RSV treatment since conventional antiinflammatory agents have failed to provide clinical benefit (35). Nonclinical studies using anti-G protein MAbs targeting the CCD motif have shown efficacy as a postinfection treatment (33,34,36,37). In a mouse model using RSV strain A2, a murine anti-G protein MAb (131-2G) administered at day 3 postinfection reduced the influx of inflammatory cells into the airways, with a pronounced effect at day 5 that was sustained to day 14 (36).…”
Section: Pharmacologymentioning
confidence: 99%
“…Passive immunisation has also proven useful, and Palivizumab, a monoclonal antibody against RSV F protein, is given to high-risk infants to prevent infection and the development of severe disease 117 . Recently, an anti-RSV G monoclonal antibody was shown to be more effective than anti-F in preventing RSV disease in animal models 118 , but this has yet to be tested in humans. Finally, maternal vaccination against RSV is an interesting future avenue for generating protection in the first month of life in newborns via placental or breast milk transfer of maternal RSV-specific antibodies to the infant 119 .…”
Section: Potential Vaccinesmentioning
confidence: 99%
“…We studied the effect of this mutation in the RSV A2 and RSV rA2 line 19F (r19F) strains in mice. The r19F strain, unlike A2, induces pulmonary mucus and airway resistance in mice (19,28,29). The effect of this mutation and treatment with the F(ab=) 2 form of the anti-RSV G 131-2G MAb show that mutating the CX3C motif to CX4C blocks much of the disease and immune modulation associated with the G protein and should improve the safety and efficacy of a live attenuated RSV vaccine.…”
mentioning
confidence: 99%